Factors influencing anti-osteoporotic medicine consumption in Uzbekistan: A descriptive analysis - Ziyodakhon Yusupova; Dilfuza Saipova (Creative Pharma Assent, 2026)
Background: Osteoporosis is an increasing public health burden in Uzbekistan, driven by demographic changes and limited access to timely diagnosis and treatment. This study aims to identify key determinants influencing the consumption of anti-osteoporotic medicines (AOMs). Methodology: A multifactor analytical approach was applied using descriptive, grouping, and correlational methods, as well as compound annual growth rate (CAGR) analysis. Because the annual series deviated from normality, associations between variables were assessed using Spearman’s rank correlation coefficient (ρ). As CAGR is a descriptive indicator, the statistical significance of temporal change was additionally evaluated using Spearman’s rank-based trend analysis. Results: Osteoporosis incidence increased by 95% between 2016 and 2024, with pronounced regional variability. The national CAGR was 9%, although the monotonic national time trend did not reach statistical significance (ρ = 0.533, p = 0.139). In RSSPMTO data, the correlation between annual population size and the combined number of osteoporosis/osteopenia cases was moderate when 2022 was included (ρ = 0.60, exact p = 0.350) and higher after exclusion of the 2022 peak (ρ = 0.80, exact p = 0.333). Still, neither association reached statistical significance, likely due to the small number of observations. Discussion: The findings indicate that medical, demographic, and technological factors, particularly limited diagnostic capacity and uneven regional detection, may influence AOMs consumption. Conclusion: Improving access to AOMs in Uzbekistan requires expanding densitometry services, implementing screening programs, and strengthening pharmaceutical policy through reference pricing, domestic production incentives, and price regulation.